2017
DOI: 10.3390/ijms18112405
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Functional Analysis of Promoters from Two Liver Isoforms of CPT I in Grass Carp Ctenopharyngodon idella

Abstract: Carnitine palmitoyltransferase I (CPT I) is a key enzyme involved in the regulation of lipid metabolism and fatty acid β-oxidation. To understand the transcriptional mechanism of CPT Iα1b and CPT Iα2a genes, we cloned the 2695-bp and 2631-bp regions of CPT Iα1b and CPT Iα2a promoters of grass carp (Ctenopharyngodon idella), respectively, and explored the structure and functional characteristics of these promoters. CPT Iα1b had two transcription start sites (TSSs), while CPT Iα2a had only one TSS. DNase I foot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…In human, Yang et al [ 8 ] confirmed that PI3KCa was transcriptionally regulated through NF-κB pathway. PPARs are key transcriptional factors which mediate the regulation of many enzymes in lipid metabolism [ 31 , 32 ]. In the present study, we identify that the PPAR-RXR binding site (located at −1788/−1767 bp of PI3KC2b promoter) is a potential positive regulator in regulating PI3KC2b promoter activity from yellow catfish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human, Yang et al [ 8 ] confirmed that PI3KCa was transcriptionally regulated through NF-κB pathway. PPARs are key transcriptional factors which mediate the regulation of many enzymes in lipid metabolism [ 31 , 32 ]. In the present study, we identify that the PPAR-RXR binding site (located at −1788/−1767 bp of PI3KC2b promoter) is a potential positive regulator in regulating PI3KC2b promoter activity from yellow catfish.…”
Section: Discussionmentioning
confidence: 99%
“…EMSA was performed to confirm the functional binding sites of HNF1, IK1 and FOXO1 according to the protocols described in our recent publications [ 32 ]. Proteins for EMSA were extracted from HepG2 cell lines.…”
Section: Methodsmentioning
confidence: 99%
“…We identified the 5 0 complementary DNA (cDNA) sequences and the transcription start sites of srebp-1, accα, scd1 and fas of grass carp using RNA ligase-mediated rapid amplification of 5 0 cDNA ends (RLM-5 0 RACE) method. The promoter cloning was performed based on the published draft genome of grass carp (18) , and the protocols followed these described in our recent studies (19) . Genomic DNA was extracted from grass carp tail fins using a commercial kit (Tissue DNA Kit; Omega).…”
Section: Cloning and Plasmids Constructionmentioning
confidence: 99%
“…For promoter luciferase assays, HepG2 cells were counted and seeded at a density of 1 × 10 5 in twenty-four well plates, then cultured and transfected as mentioned in our recent studies (19,23) . Briefly, to study the nSREBP-1-induced changes in promoter activities, we co-transfected 300 ng of nSREBP-1 plasmid or the same amount of pcDNA3.1(þ) plasmid (300 ng, control) with 500 ng of each of these luciferase reporter plasmids of srebp-1, accα, scd1 and fas promoters into HepG2 cells using Lipofectamine 2000 (Invitrogen) at 80-90 % confluence, respectively.…”
Section: Luciferase Assay Of Srebp-1 Accα Scd1 and Fas Promotersmentioning
confidence: 99%
“…At present, studies on the promoters of lipid metabolism-related genes are scarce in fish. Recently, in our laboratory, Xu et al [ 17 ] analyzed the structure and function of CPT I promoter in grass carp, but no studies have been reported for the promoter structure and function of ACCα , FAS , and PPARγ in teleosts.…”
Section: Introductionmentioning
confidence: 99%